ANALISIS POTENSI PENDAPATAN USAHA KARAKA DAN IKAN DI KABUPATEN MIMIKA - Riski Ali; Tharsisius Pabendon (JURNAL ULET (Utility, Earning and Tax), 2019)
This study aims to determine the value of income potential in crab and fish businesses in Mimika Regency. The research method used is descriptive and comparative research methods. In this study the data collection methods used were observation methods, questionnaire methods, documentation methods and library methods. To find out the differences in the potential income of crab and fish, the data analysis instrument used is profitability ratio analysis and different test. The results of this study indicate that the net profit margin of the average business is 3.01% / month while the net profit margin of the average fish business is 12.25% / month. There is a difference in the average net profit margin between the business and the fish business where the net profit margin of the average business is lower than the net profit margin of the average fish business per month.